FUNDAMENTAL ECONOMIC RISK FACTORS IN INCREASING THE VALUE OF DIGITAL ASSET INVESTMENTS IN INDONESIA - Reza Juanda; Falahuddin; Muttaqien; Rico Nur Ilham; Frengki Putra Ramansyah; Muhammad Multazam (Universitas Efarina, 2024)
Already has a permit to be traded in exchange trading through the Indonesian Commodity Futures Trading Supervisory Agency (BAPEPTI). Digital crypto assets traded in Indonesia are quite a lot through the Indodax trading company. The purpose of this study is focused on formulating a risk management process in investing in digital cryptocurrency assets. In addition, the results of this study will produce policy recommendations known as LCTR or